Gale's Fixed Tax for Exchanging Houses - Tommy Andersson; Lars Ehlers; Lars-Gunnar Svensson; Ryan Tierney (Lund University, School of Economics and Management, Department of Economics, 2021)
We consider taxation of exchanges among a set of agents where each agent owns one object. Agents may have different valuations for the objects and they need to pay taxes for exchanges. We show that if a rule satisfies individual rationality, strategyproofness, constrained efficiency, weak anonymity and weak consistency, then it is either the no-trade rule or a fixed-tax core rule. For the latter rules, whenever any agent exchanges his object, he pays the same fixed tax (a lump sum payment which is identical for all agents) independently of which object he consumes. Gale's top trading cycles algorithm finds the final assignment using the agents' valuations adjusted with the fixed tax if the induced preferences are strict.
Keywords: C71; C78; D63; D71; D78; 330; Fixed Tax; Exchanges; Top Trading